Ethiopia : Modelling the Impact of Tobacco Tax Policy Reforms on Tobacco Use and Domestic Resources Mobilization Under Different Scenarios - World Bank Group (World Bank, Washington, DC, 2019)
As part of the ongoing tax policy dialogue with the Government of Ethiopia, the World BankGroup organized a workshop in Addis Ababa, on June 20, 2016, to discuss tobacco use, its healthimpact, and excise taxes on tobacco as a public policy measure to reduce tobacco use, and hencethe risk of ill health, premature mortality, and disability due to tobacco-related diseases, andmobilize additional domestic resources to expand the fiscal capacity of the government, inaccordance with the Financing for Development Addis Ababa Action Agenda. This event wasattended by officials from the Ministry of Health (MOH) and Ministry of Finance & EconomicCooperation (MoFEC). Ethiopia's Health Sector Transformation Plan 2015-2020 lists noncommunicable diseases (NCDs) as one of the major public health challenges facing the country. As in the rest of sub-Saharan Africa, NCDs are expected to become the leading cause of ill health and death by 2030, influenced by rapid urbanization, rapid per capita economic growth, increase in behavioral risk factors (most NCDs are the result of tobacco use, physical inactivity, unhealthy diet, and/or the harmful use of alcohol), and improvements in the control of infectious diseases that increase life expectancy. As NCDs have become a major health burden in the country, the Government has put in place ambitious targets to reduce the prevalence of the main health risk factors associated with the onset of NCDs among the population. The strategy focuses on increasing prevention and control of the main risk factors: tobacco use and alcohol abuse, physical inactivity and unhealthy diet, which contribute to about 80 percent of NCDs.